2009
DOI: 10.4020/jhrs.25.16
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Meaning of Right Bundle Branch Block Pattern on Surface Electrocardiogram in Pacemaker Patients During Right Ventricular Endocardial Pacing

Abstract: Introduction: Right bundle branch block (RBBB) pattern is sometimes observed in right ventricular (RV) endocardial pacing. However, the true mechanism and the clinical meaning of this phenomenon are still unknown.Methods and results: Out of 218 consecutive patients with RV apex endocardial pacing, we studied 30 cases with RBBB pattern and 111 cases with left bundle branch block (LBBB) pattern. No significant differences were found between these 2 groups in age, sex, and pacing mode. However, the percentage of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…5 Lastly, severe disease of the right bundle conducting system could result in earlier penetration of the paced electrical impulse into the left ventricular conduction system, with a resultant RBBB pattern on ECG. 6 , 7 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Lastly, severe disease of the right bundle conducting system could result in earlier penetration of the paced electrical impulse into the left ventricular conduction system, with a resultant RBBB pattern on ECG. 6 , 7 …”
Section: Discussionmentioning
confidence: 99%
“…The more likely explanation is that the tip of the pacing electrode is in the most posterior portion of the right ventricle, on the interventricular septum, relatively far from the chest wall and early precordial chest leads (ie, V 1 –V 3 ). 6 , 7 Klein and colleagues 2 reported that recording an ECG with the V 1 and V 2 leads in the fifth or sixth intercostal space unmasks an LBBB pattern with true apical right ventricular pacing. 2 This maneuver was performed in both patients.…”
Section: Discussionmentioning
confidence: 99%